Adverse effects of pre-existing cerebral small vessel disease on cognitive improvement after carotid endarterectomy. Issue 6 (August 2020) - Yoshida, Jun; Yamashita, Fumio; Sasaki, Makoto; Yoshioka, Kunihiro; Fujiwara, Shunrou; Kobayashi, Masakazu; Yoshida, Kenji; Kubo, Yoshitaka; Ogasawara, Kuniaki
Background: Although patients with improved cognition after carotid endarterectomy usually exhibit postoperative restoration of cerebral blood flow, less than half of patients with such cerebral blood flow change have postoperatively improved cognition. Cerebral small vessel disease on magnetic resonance imaging is associated with irreversible cognitive impairment. Aims: The purpose of the present prospective study was to determine whether pre-existing cerebral small vessel disease affects cognitive improvement after carotid endarterectomy. Methods: Brain MR imaging was performed preoperatively, and the number or grade of each cerebral small vessel disease was determined in 80 patients undergoing carotid endarterectomy for ipsilateral internal carotid artery stenosis (≥70%). The volume of white matter hyperintensities relative to the intracranial volume was also calculated. Brain perfusion single-photon emission computed tomography and neuropsychological testing were performed preoperatively and two months postoperatively. Based on these data, a postoperative increase in cerebral blood flow and postoperative improved cognition, respectively, were determined. Results: Logistic regression analysis using the sequential backward elimination approach revealed that a postoperative increase in cerebral blood flow (95% confidence interval [CI], 10.74–3730.00; P  = 0.0004) and the relative volume of white matter hyperintensities (95% CI, 0.01–0.63; P  = 0.0314) were significantly associated with postoperative improved cognition. Although eight of nine patients with postoperative improved cognition exhibited both a relative volume of white matter hyperintensities <0.65% and a postoperative increase in cerebral blood flow, none of patients with a relative volume of white matter hyperintensities ≥0.65% had postoperative improved cognition regardless of any postoperative change in cerebral blood flow. Conclusion: Pre-existing cerebral white matter hyperintensities on magnetic resonance imaging adversely affect cognitive improvement after carotid endarterectomy.